Highly Conductive All‐Plastic Electrodes Fabricated Using a Novel Chemically Controlled Transfer‐Printing Method. (23rd February 2015) - Kim, Nara; Kang, Hongkyu; Lee, Jong‐Hoon; Kee, Seyoung; Lee, Seoung Ho; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> A novel transfer‐printing method for high‐performance all‐plastic transparent electrodes is demonstrated. A solution process using H2SO4 not only dramatically enhances the electrical conductivity of poly(3, 4‐ethylenedioxythiophene):poly(4‐styrenesulfonate) (PEDOT:PSS) over 4000 S cm−1 but also chemically modifies its adhesion properties, thereby enabling expeditious "pick‐and‐place" transfer onto arbitrary surfaces using elastomeric stamps. Flexible and transparent optoelectronic devices with transferred PEDOT:PSS electrodes show superb performances. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>